2020
DOI: 10.7554/elife.55582
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of neuronal and lymphoid cannabinoid CB2 receptors in neuropathic pain

Abstract: Cannabinoid CB2 receptor (CB2) agonists are potential analgesics void of psychotropic effects. Peripheral immune cells, neurons and glia express CB2, however the involvement of CB2 from these cells in neuropathic pain remains unresolved. We explored spontaneous neuropathic pain through on-demand self-administration of the selective CB2 agonist JWH133 in wild-type and knockout mice lacking CB2 in neurons, monocytes or constitutively. Operant self-administration reflected drug-taking to alleviate spontaneous pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…In support of our finding of neuron CB2R function, European labs generated principle neuron-specific Syn-Cnr2 Δ mouse strain by crossing Cnr2 f/f strain with Syn-Cre-deleter mouse strain [ 38 ]. Electrophysiological and behavioral studies of Syn-Cnr2 Δ mice found that the activation of neuronal CB2R enhanced a long-lasting membrane potential hyperpolarization by activating autonomous slow self-inhibition in neurons of hippocampus and cortex [ 38 , 39 ] and reduced neuropathic pain and anxiety [ 40 ]. By crossing the Cnr2 f/f strain with monocyte-specific LysM-Cre-deleter mice to generate LysM-Cnr2 Δ cKO mice [ 40 ], the authors found that both lymphocyte and neuron CB2Rs participate in coordinated functions in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of our finding of neuron CB2R function, European labs generated principle neuron-specific Syn-Cnr2 Δ mouse strain by crossing Cnr2 f/f strain with Syn-Cre-deleter mouse strain [ 38 ]. Electrophysiological and behavioral studies of Syn-Cnr2 Δ mice found that the activation of neuronal CB2R enhanced a long-lasting membrane potential hyperpolarization by activating autonomous slow self-inhibition in neurons of hippocampus and cortex [ 38 , 39 ] and reduced neuropathic pain and anxiety [ 40 ]. By crossing the Cnr2 f/f strain with monocyte-specific LysM-Cre-deleter mice to generate LysM-Cnr2 Δ cKO mice [ 40 ], the authors found that both lymphocyte and neuron CB2Rs participate in coordinated functions in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological and behavioral studies of Syn-Cnr2 Δ mice found that the activation of neuronal CB2R enhanced a long-lasting membrane potential hyperpolarization by activating autonomous slow self-inhibition in neurons of hippocampus and cortex [ 38 , 39 ] and reduced neuropathic pain and anxiety [ 40 ]. By crossing the Cnr2 f/f strain with monocyte-specific LysM-Cre-deleter mice to generate LysM-Cnr2 Δ cKO mice [ 40 ], the authors found that both lymphocyte and neuron CB2Rs participate in coordinated functions in neuropathic pain. An intriguing observation is that lymphocytes participate in CB2R induced antinociception by infiltration into dorsal root ganglia (DRG) of the injured nerve and transferred their high gradient CB2R to low gradient neuron CB2R [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, another study suggested that rather neuronal and lymphoid and not myeloid CB2R is important for nociception after PNL [98]. This was shown by an increase in self-administration of a selective CB2R agonist, and an increased nociception after deletion of CB2R from neurons, but not from myeloid cells.…”
Section: Neuropathic Painmentioning
confidence: 98%
“…As far as we know two groups independently generated Cnr2 fl/fl animals [21,124]. Up to date Cnr2 fl/fl were further crossed with three different cre-expressing mouse lines: Syn1-cre (B6.Cg-Tg(Syn1-cre)671Jxm/J) for neuron-specific deletion [21,97,98], DAT-cre for a specific deletion in midbrain dopaminergic neurons [124] and LysM-cre (B6.129P2-Lyz2 tm1(cre)Ifo/J) animals for CB2 deletion in myeloid cells [97,98].…”
Section: Cb2 Knockout Mouse Linesmentioning
confidence: 99%